Effect of Inclusion of Garlic (Allium sativum) Powder at Different Levels and Copper into Diets of Hens on Performance, Egg Quality Traits and Yolk Cholesterol Content - Kaya, Hatice; Macit, Muhlis (International Journal of Poultry Science, 2012)
This experiment was conducted to investigate the effects of inclusion of oven dried garlic powder (Allium sativum) at different levels and copper into diets of hens on performance, egg quality traits, yolk and serum cholesterol content. A total of 240 Lohmann white layers, 38 wks of age, were allocated randomly eight groups, each formed 6 replicate cages as subgroups, comprising of five hens. Treatment groups were fed diets containing a standard commercial layer diet, basal diet plus 200 ppm copper (CuSO4.5H2O), 2% garlic powder, 2% garlic powder + 200 ppm copper, 4% garlic powder, 4% garlic powder + 200 ppm copper, 6% garlic powder and 6% garlic powder + 200 ppm copper from week 38th to 50th. Feed conversion efficiency and cracked egg were not affected by feeding garlic powder and copper. Egg weight, egg production and feed consumption decreased with garlic powder and copper supplementation. There were no differences in the egg quality traits except for shell stiffness and yolk index. Egg yolk cholesterol concentration decreased linearly with increased levels of garlic powder but serum cholesterol concentration increased. The supplementation of 200 ppm copper and combinations of garlic powder and copper did not have a significant effect on cholesterol and triglyceride concentrations of egg and serum. Consequently, without having a significant effect on laying performance and egg quality characteristics, oven dried garlic powder can be used up to 6% as a hipocholesterolemic agent in practical layer diets without copper.